Effectiveness of the Technological Approach in the Spiritual Life of Young People - Majitovna, Rakhmatova Mekhrinoz (International Journal on Integrated Education, 2024)
This article explores the effectiveness of integrating technological approaches in the spiritual development of young people. The study examines how technology can be utilized to enhance spiritual practices, foster personal growth, and promote positive well-being among youth. Various technological tools and platforms are analyzed for their potential impact on the spiritual lives of young individuals. The findings suggest that incorporating technology in spiritual activities can be beneficial in engaging and empowering young people to deepen their spiritual connections and values. The implications of this technological approach on the overall well-being and development of youth are discussed, highlighting the importance of embracing innovative strategies in addressing the spiritual needs of the younger generation.